Cethrene: A Helically Chiral Biradicaloid Isomer of Heptazethrene. Issue 3 (23rd November 2015) - Ravat, Prince; Šolomek, Tomáš; Rickhaus, Michel; Häussinger, Daniel; Neuburger, Markus; Baumgarten, Martin; Juríček, Michal
Abstract: We report the synthesis and properties of "cethrene", the only helically chiral isomer of heptazethrene with a biradicaloid singlet ground state. Cethrene gives a well‐resolved EPR spectrum at room temperature and its structure was confirmed by 2D NMR and absorption spectroscopies. Our experiments and calculations show that the helical twist affects its electronic properties and decreases the singlet–triplet energy gap when compared to that of planar heptazethrene. Cethrene undergoes an intramolecular cyclization within several hours at room temperature. Abstract : "C" versus "Z" : In chiral biradicaloid cethrene ("C") the singlet–triplet energy gap is smaller than that in planar heptazethrene ("Z") because of the helical twist. Cethrene gives well‐resolved EPR and NMR spectra and its structure was confirmed by 2D NMR spectroscopy. The helical compound undergoes a transformation to a planar hydrocarbon and "lives" for several hours at room temperature.